(RETRACTED) THE MEDIATING EFFECT OF SHARIA COMPLIANCE ON THE RELATIONSHIP BETWEEN GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, AND FINANCIAL PERFORMANCE IN INDONESIAN ISLAMIC BANKS - Mohamed, Liban Isak; Tubastuvi, Naelati (Universitas Muria Kudus, 2024)
Reasons for Retraction:The editors have retracted this article at the request of the authors due to internal conflicts among the authors. This decision was made to preserve the integrity of the research and to address the issues raised in good faith. The authors unanimously agreed to withdraw the publication to resolve the conflicts effectively.